The biography genre: a proposal of work from the rewriting process - Esper, Débora Sodré; Hila, Cláudia Valéria Doná (Acta Scientiarum. Language and Culture, 2015)
This article aims to show a proposal of work with the biography genre together with text revision. It is based on studies related to the teaching-learning process of text production and on the theory of discourse genres (BAKHTIN, 1997). This work made use of 19 compositions by students of the 4th grade of Elementary School (ES) from a private school of Maringá, Paraná State, and counted with the conduction of a survey on the main problems shown; from the results, a series of activities aiming at the learning of the genre referred was proposed.